Sekolah Alam di Kalsel; Latar Belakang, Ekspektasi dan Persepsi - Ramadan, Willy (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This study aims to identify the background, expectations and perceptions of parents sending their children to SD Alam Muhammadiyah and students in attending education at the Nature School The method in this research is qualitative with a case study approach.. Data collection techniques in this study through interviews, observation, documentation and field notes. The results of this study found that the background that influenced parents decided to send their children to SD Alam can be concluded for several reasons, namely Distrust, Past Experience, Word of Mouth Communication, External Communications, Personal Need and Institutional. While the background of school students in SD Alam is due to the reasons for the Parent Need and School Environment. The expectations of parents is that children have a strong religious foundation. Children have social intelligence, children have good morals / characters, have abilities in sports, schools can direct children to have their own unique and creative talents, supply of available books and the construction of SMP and SMA Alam. Whereas students 'expectations, namely extracurricular programs, are reproduced and students' self-development programs are more often implemented. In the aspect of parental perception is the concept of nature-based schools that are fun and interesting for children, the portion of religious education is more, the rules are more flexible than state schools, prioritizing religious values, character and creativity and do not distinguish between social status and condition of children. While the perception of children is school, teachers and subjects are fun and many extracurricular.